COMPARATIVE ANALYSIS OF GENDER RELATED ISSUES IN THE NOVEL THE AGE OF INNOCENCE BY EDITH WARTHON AND BIG LITTLE LIES BY LIANE MIROARTE - Kadir, Riskawanti; Nur, Sahril; Nurfadhilah, Auliyanti S (ELITERATE : Journal of English Linguistics and Literature Studies, 2022)
The aims of this research is to find out the different perspectives of two female authors in the novel The Age of Innocence and Big Little Lies. The researcher has compared these novels to find out the different types of women language, the impact of social norm, and how the marriage lives of the main characters. This research used descriptive qualitative research in order to describe the phenomenon and its characteristics that are related to the topic. Using the Lakoff’s theory, the researcher has categorized women language of main women characters using the theory of Women by Lakoff. The researcher applied feminism approach to find out practical of liberal feminism as the effect of social norms, rules and habit in these two novels.  The result of this study indicates that there are 8 types of women language using in The Age of Innocence and 5 types of women language using in Big Little Lies based on Lakoff theory. Then, social norms are very affected to the characters life in these two novels. The Age of Innocence shows old era while Big Little shows modern era. The marriage is very crucial things in the Age of Innocence while in Big Little Lies the marriages is complicated. The freedom to speak up is related to the social norms and rules applied in that place.